The potential effect of gut microbiota on the secretion of selected cytokines by human cells in vitro - Kopa-Stojak, Paulina Natalia; Kleniewska, Paulina; Hoffmann, Arkadiusz; Pawliczak, Rafał (Scientific reports, 2025)
Colonization of the gut early in life plays a significant role in guiding the development of the immune system. The effect of individual intestinal bacterial strains on the asthma development is the subject of numerous scientific studies. The aim of the study was to determine the role and the potential mechanism of action of intestinal microflora on secretion of cytokines and potential predisposition to asthma development. The effect of Parabacteroides distasonis (PD) , Bacteroides vulgatus (BV) Clostridium perfringens (CP) and Ruminococcus albus (RA) lysates on the secretion of IL-4, IL-5, IL-8 (CXCL8) and IL-13 in human peripheral blood mononuclear cells, monocytes and HT-29 cells has been analyzed by enzyme-linked immunosorbent assays. RA and PD 400 µg lysates significantly increased secretion of IL-5 by PBMC compared to control ( p < 0.05). In addition, BV, CP, PD and RA 100 µg lysates significantly increased IL-8 secretion by PBMC, as well as BV, PD and RA 100 µg lysates by monocytes compared to control ( p < 0.05). Moreover, PD 100 µg and 400 µg lysates significantly increased secretion of IL-8 by HT-29 cells compared to BV 100 µg and 400 µg lysates ( p < 0.05). CP, BV, PD and RA 100 µg lysates significantly lowered IL-13 secretion by PBMC vs. control ( p < 0.001). For a better understanding of the mechanisms of action of gut microflora and their impact on parameters important in asthma, complex studies which compare the asthma and control samples should be carried out in the future.